Effect of Application of Liquid Organic Fertilizer of Pineapple Peel Waste on Growth and Production of Red Lettuce Plants (Lactuca sativa var. Crispa): Pengaruh Aplikasi Pupuk Organik Cair Limbah Kulit Nanas Terhadap Pertumbuhan Dan Produksi Tanaman Selada Merah (Lactuca sativa var. Crispa) - Kuswardina, Atik; Abror, M (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of giving the optimal concentration of pineapple peel liquid organic fertilizer on the growth and production of red lettuce plants (Lactuca sativa var. Crispa)